Food security and economic development in the Middle East and North Africa: Current state and future perspectives - Breisinger, Clemens; van Rheenen, Teunis; Ringler, Claudia; Nin-Pratt, Alejandro; Minot, Nicholas; Aragon, Catherine; Yu, Bingxin; Ecker, Olivier; Zhu, Tingju (International Food Policy Research Institute, 2010)
A rapidly changing world combined with mounting domestic challenges is prompting many Middle East and North African (MENA) countries to rethink their development models and to initiate economic and social reforms. Taking this new momentum as a starting point, this paper uses the concept of Food Security to identify the region's challenges along four major themes: economic growth and incomes, trade and infrastructure, agriculture and water, and health and education. Results show that many of the region's longstanding challenges persist; yet taking immediate action is more urgent in light of the recent, global food, fuel, and financial crisis and projected severe impacts of climate change. Fostering development and achieving food security will require economic growth and diversification that generates jobs for the majority of people, breaking the strong vulnerability to international oil and food price volatility, managing depleting water resources and climate change adaptation effectively, transforming social policies to target the poor, and empowering women to play a more active role in the economy and society. Designing policies and investments for achieving progress in this direction are most likely to be successful if based on lessons from the past, successful countries' experiences and research-based strategic analysis. The paper therefore concludes with a list of priority research areas to identify key actions to be taken on regional, national and sub-national levels to foster development and food security.